1997
DOI: 10.1161/01.cir.95.5.1231
|View full text |Cite
|
Sign up to set email alerts
|

Configuration of Unipolar Atrial Electrograms During Electrically Induced Atrial Fibrillation in Humans

Abstract: The morphology of single unipolar electrograms during AF reflects the occurrence of various specific patterns of conduction. This might be used to differentiate between different types of AF and to identify regions with structural conduction disturbances involved in perpetuation of chronic AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
339
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(357 citation statements)
references
References 42 publications
14
339
1
2
Order By: Relevance
“…10,11 However, the studies by Cox et al 10 did demonstrate the presence of unstable reentrant circuits, principally in the RA, which could be interpreted as causing fibrillatory conduction to the LA and parts of the RA. Likewise, the studies by Konings et al 11 demonstrated 3 activation patterns in the RA, 1 of which included the presence of an unstable reentrant circuit of short CL that may have served as a driver, causing fibrillatory conduction.…”
Section: Patterns Of Activation During Af In Humansmentioning
confidence: 99%
“…10,11 However, the studies by Cox et al 10 did demonstrate the presence of unstable reentrant circuits, principally in the RA, which could be interpreted as causing fibrillatory conduction to the LA and parts of the RA. Likewise, the studies by Konings et al 11 demonstrated 3 activation patterns in the RA, 1 of which included the presence of an unstable reentrant circuit of short CL that may have served as a driver, causing fibrillatory conduction.…”
Section: Patterns Of Activation During Af In Humansmentioning
confidence: 99%
“…An increase in regularity implies the existence of local activation waves with a decrease of complexity, which is related to the existence of lesser complex activation patterns [24]. Moreover, the upper relevance of the features related to standard deviation of NE and NO showed that the dispersion in the wave morphology and spectral complexities are essential to characterize the benefits of PE.…”
Section: Feature Selection Analysismentioning
confidence: 99%
“…From type I to type III, the frequency and irregularity of AF increased, and the incidence of continuous electrical activity and reentry became higher (Konings et al, 1994). Electrogram morphology was found to be an indicator for collision of wavefronts (short double potentials), conduction block (long double potentials), and pivoting points or slow conduction (fragmented potentials) (Konings et al, 1997) and (Kottkamp & Hindricks, 2007). Unfortunately, mapping of high-dominant-frequency areas has been shown not to be effective in chronic AF patients (Sanders et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Nademanee et al (Nademanee et al, 2004) sought to investigate the electrophysiological substrate and referred in their publication introduction to the work of Allessie's group. In a landmark publication, Konings et al (Konings et al, 1997) described high-density mapping of electrically induced AF in patients with Wolff-Parkinson-White syndrome undergoing surgery using a spoon-shaped electrode with 244 unipolar electrodes. In that study, the right atrium was investigated and was found to be activated by one or multiple wavelets propagating in different directions.…”
Section: Introductionmentioning
confidence: 99%